(untitled) (International Journal of Innovative Computing, 2023)
Servers are essential in this current digital world as the mainstay communication between human and the desired services and information. Its existence and usage of course highlight the requirement to secure it both physically and also through the digital space. This is of course a well known and accepted. Another essential needed in ensuring that services are not interrupted is through the well-being of the servers themselves. Due to the amount of processing a server does, it tends produce heat, which have to be managed to prevent overheating, and thus ensuring that it can continue to its job. The server room also needs full maintenance supervision, as every component and tool supplied must be in good condition. The temperature and humidity of the server room must be in a stable state to prevent electronic components from getting wet and causing rust. Therefore, this project will discuss and develop a device that can prevent such issues. The developed device can read the room temperature and humidity accurately and control the air conditioner’s temperature for temperature stability to be in the proper condition. This device is also capable of sending and reading data to a database. As a result, users can monitor the server room temperature from different places. This project can help reduce the workload of employees without any time wasted continuously and manually checking the conditions.